Between Devotion and Precarity: Religious Calling, Moral Resilience, and Livelihood Strategies among Underpaid Madrasah Teachers - Taufikin Taufikin (Al-Qalam Institue, 2023)
This study examines how underpaid teachers in private Islamic junior secondary schools (madrasah tsanawiyah) in rural Indonesia make sense of their profession amid persistent economic constraints. Against a broader context of precarious educational labor and limited welfare provision, the research explores how religious values shape teachers’ commitment and coping strategies. Using a qualitative approach with an interpretative phenomenological design, data were collected through observations of 62 teachers and in-depth interviews with six teachers and two school principals in Demak. Thematic analysis was conducted through open, axial, and selective coding. The findings reveal that teaching is constructed not merely as employment but as a religious calling and moral devotion, fostering a form of moral resilience that sustains teachers despite low and unstable income. At the same time, teachers engage in hybrid livelihood strategies—including farming, small-scale trading, and informal work—to meet their economic needs while maintaining their pedagogical identity. However, this moral framing also risks normalizing structural inequality and symbolic exploitation. This study contributes to the literature by proposing the concept of “moral resilience through religious calling” within a moral economy of teaching, integrating religious, economic, and educational dimensions in understanding teacher sustainability in the Global South.